If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m+3(m-3)=m/2
We move all terms to the left:
m+3(m-3)-(m/2)=0
We add all the numbers together, and all the variables
m+3(m-3)-(+m/2)=0
We multiply parentheses
m+3m-(+m/2)-9=0
We get rid of parentheses
m+3m-m/2-9=0
We multiply all the terms by the denominator
m*2+3m*2-m-9*2=0
We add all the numbers together, and all the variables
-1m+m*2+3m*2-18=0
Wy multiply elements
-1m+2m+6m-18=0
We add all the numbers together, and all the variables
7m-18=0
We move all terms containing m to the left, all other terms to the right
7m=18
m=18/7
m=2+4/7
| 3(4a-a)=2(a+6) | | 3x+2=111 | | 3(x+2)=111 | | (x)+(x+1)+(x+2)=111 | | 10x+6=6x+1 | | x)+(x+2)+(x+3)=111 | | 4x+12-x+9=51 | | -x+7=x-7 | | 12/k=18/42 | | 8m/6=0 | | 9=-d+18 | | 3m+8=6m+4 | | -0.6(5-2y)=-3(y-5)-18 | | −3(y+2)=21 | | 2(x-6)+3=4+x* | | 8b-4=-2b+9 | | n*9=22 | | 5w^2=-8w-2 | | 7x(4x-1)=0 | | 14=-7/6y | | 6x-4=2x+1+3x+7 | | -10n-6=-2n-6 | | 3x+2+(15x-9)=180 | | 2/5(x+4)+(-7)=-16 | | V+6=v+8 | | x(8+2)+3=2(5+x)+5(x+1-6 | | -7/5w=-28 | | 8x+3=5x-27 | | 3.78=3x | | -2v/3=-8 | | 3v-10=3v-10 | | 11/x=13/8 |